Przekład intersemiotyczny. Przypadek znaku drogowego, ekfrazy i adaptacji filmowej - Kloch, Zbigniew (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article is an attempt to clarify and refine the ways of understanding two basic types of translation: from one language into another ethnic language (translation proper) – i.e. following the principles of translating homo- geneous systems of signs – and from one system of signs to another, e.g. verbal to iconic, or vice versa, which is sometimes called transmutation. Therefore, the starting point for the discussion is Roman Jakobson’s well-known typology of translation, which also took into account cases of intralingual translation within the same language, called rewording. However, the article mainly focuses on various cases of intersemiotic translation and thus transmutation, meaning situations where a text expressed in one system of signs is translated into a system of a different nature. The primary research question concerns what is actually being translated in such a situation and how this type of translation differs from a typical language-to-language translation. The article is chiefly theoretical, and the examples concern the cases of translating verbal signs into iconic ones, such as the rules governing traffic into a road sign, the translation of an image (a painting, photography) into a literary text (ekphrasis and its varieties), and a film adaptation. The equivalence of codes secures the adequacy of a linguistic translation. In the case of ekphrasis, the image is usually replaced by a verbal narrative, and in a film adaptation, the type and sequence of iconic signs must simply be invented because these sign systems are not directly equivalent, as Benveniste and Lotman believe. Examples that illustrate the main theses of the article are Jacek Kaczmarski’s art-inspired songs, several film adaptations of Shakespeare’s Macbeth (Polański, Kurosawa), and Agnieszka Holland’s film adaptation (Pokot [Spoor]) of one of Olga Tokarczuk’s novels.